Aktor Komunikasi Dakwah Digital dalam Pembentukan Citra Destinasi Wisata di Pulau Lemukutan, Bengkayang, Kalimantan Barat - Fajar Abdurrahman; Bob Andrian; Muhammad Khalil Gunawan; Hariyanto; Riduan Riduan (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2026)
This study aims to analyze digital da'wah communication and destination image construction in religious tourism on Lemukutan Island, West Kalimantan, through a digital ethnographic perspective. This research is motivated by the limited studies that connect digital da'wah, User Generated Content (UGC), and the construction of the image of religious tourism destinations in the context of new media culture. The research uses a qualitative approach with digital ethnographic methods through observation of social media TikTok, Instagram, Facebook, and YouTube. The results of the study show that tourists no longer only play the role of tourism consumers, but also as digital da'wah communication actors who actively produce and disseminate religious narratives, spiritual experiences, and destination images through social media. The practice of digital da'wah on Lemukutan Island develops in a participatory manner through the involvement of tourists, religious leaders, and local communities in forming representations of religious tourist destinations on social media. This study also found that social media has a strategic role in strengthening the image of Lemukutan Island as a natural, religious, and authentic tourist destination, but at the same time has the potential to encourage the commodification of religious and cultural symbols due to the logic of digital media virality. Theoretically, this research contributes to the development of a conceptual model of digital da'wah communication actors in the study of tourism communication and digital culture. Practically, the results of this study can be a reference for local governments and tourism managers in designing religious tourism communication strategies that are adaptive to the dynamics of social media. This research is limited to the scope of location and number of informants, so further research is needed with a cross-platform approach and comparison between digital religious tourism destinations at the global level.